Development of Deep Learning Approach-Based Teaching Materials for Fostering Peace-Loving Character in Elementary School Students - Fauzi Giwangsa, Sendi; Saddam nurob, Faisal; Maulidah, Neni; Fauziana Ridwan, Aji; Destiana Agusman, Desi; Sulistyowati, Gadis; Nur Chikal Hergiana, Syadni (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: The widespread phenomenon of bullying in Indonesian elementary schools, with 41.1% of students experiencing harassment, demonstrates the urgent need for effective character development. The deep learning approach, which emphasizes meaningful, mindful, and joyful learning, offers an innovative solution for developing students' peace-loving character. This study aims to develop teaching materials based on the deep learning approach to foster peace-loving character as an effort to prevent bullying behavior in elementary school students. The research employs a Design and Development (D&D) approach using the PPE (Planning, Production, Evaluation) method. The planning stage includes needs analysis, curriculum analysis, and literature review. The production stage develops teaching materials based on deep learning principles. The evaluation stage involves validation by material, media, and language experts through focus group discussions (FGD). The product consists of teaching materials titled